TRANSPOSITION AND ITS IMPACT ON TRANSLATION QUALITY IN THE BOOK YOU WISH YOUR PARENTS HAD READ - Ayu Awanda; Mangatur Nababan; Riyadi Santosa (University of Kuningan, 2025)
Sentence shifts often occur when a sentence in the source language cannot be directly translated into the target language without altering the meaning or message of the source language. This research investigates sentence-level and its types of transpositions in The Book You Wish Your Parents Had Read and examines their influence on translation quality in terms of accuracy, acceptability, and readability. A qualitative method with a single-embedded case study design was used to gather the data from transposed sentences. Findings revealed a predominance of downward rank shifts (189 instances) over upward rank shifts (15 instances), indicating the translator’s tendency to simplify complex source structures into more concise target-language forms. The translation quality achieved high scores in accuracy (2.9) and readability (2.9), suggesting that the intended meaning was preserved and the text remained easy to comprehend. However, acceptability scored slightly lower (2.7), implying that some lexical and syntactic choices did not fully conform to the cultural and linguistic norms of the target language. With an overall mean score of 2.8, the translation is categorised as “good” but could be improved through refined vocabulary selection, enhanced idiomatic expressions, and greater cultural adaptation. These findings highlight the functional role of transposition in balancing semantic fidelity, naturalness, and clarity in English–Indonesian translation.